Perbedaan Peningkatan Hasil Belajar Melalui Modul Berbasis Website pada Pemrograman Web Dasar - Nalendra Arya Putra Pratama; Ipan Ripai (PEDAGOGIC: Indonesian Journal of Science Education and Technology, 2026)
The integration of digital learning resources in vocational education requires evaluation based on measurable learning outcomes. This study aims to examine differences in students’ learning improvement associated with the use of a website-based learning module in the Basic Web Programming subject. A quantitative approach with a quasi-experimental nonequivalent control group design was employed. The sample consisted of 58 students, including 26 in the experimental class and 32 in the control class. The instrument was a 20-item multiple-choice test, supported by a student response questionnaire. Data analysis used gain scores as the primary indicator, followed by the Shapiro–Wilk normality test and the Mann–Whitney U test. The results of the analysis indicate that the improvement in student learning outcomes in the experimental class was statistically higher than in the control class, with a significant difference () and a moderate effect size. Furthermore, student responses to the use of the web-based module fell into the good to very good category. These findings indicate that web-based learning modules have a significant effect on improving student learning outcomes and have practical implications for programming education, although the limitations of the quasi-experimental design must still be taken into account